Analisis Pengaruh Risiko, Tingkat Efisiensi Dan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Yang Terdapat Di Jakarta Islamic Index - Sarawati, Nita; , Muhammad Sholahuddin, S.E. M.Si (2015)
This study aimed to analyze the influence of risk (erning per share), the level of efficiency (return on assets) and good corporate governance (selfassessment) toward the level of financial performance measured by carrentratio. The population used in this study is a company registered in Jakarta Islamic Index. The samples are 18 companies listed in the Jakarta Islamic Index 2011- 2013. The sample used purposive sampling technique. The data in this research is secondary data obtained from financial statements and annual report of the company. The method of analysis used multiple linear regression to determine the effect of risk (erning per share), the level of efficiency (return on assets) and good corporate governance (self-assessment) to the level of financial performance (carrent ratio).Based on test results by using multiple linear regression analysis, the results of t-test showed the risk (erning per share) does not significantly affect the company's financial performance (carrent ratio). Level of efficiency (return on assets) have a significant effect on financial performance (carrent ratio) and good corporate governance (self-assessment) significantly affects the level of financial performance (carrent ratio). While based on simultaneous test (F test) risk (erning per share), the level of efficiency (return on assets) and good corporate governance (self-assessment) significantly affects the level of financial performance (carrent ratio).